Вариации „мистической реальности“ Федора Достоевского в романе Sous le soleil de Satan Жоржа Бернаноса - Dzyk, Roman (Masaryk University, 2022)
The article under studies deals with the issue of connotation of the phenomenon of the "mystical" with literary experience. It outlines the significance of literature as a prevailing verbal "tool" of penetration into the field of the mystical. Particular emphasis in the article has been laid on the implementation of the ideological analogies between Georges Bernanos and Fyodor Dostoevsky at the level of text poetics, in terms of determining the nature and semantic content of the notion of "realism". The French writer's novel Under the Sun of Satan (Sous le soleil de Satan, 1926) has been regarded as an illustrative example.
Fyodor Dostoevsky’s Variations of “Mystical Reality” in the Novel Sous le soleil de Satan by Georges Bernanos
Keywords: Fyodor Dostoevsky; realism; the mystical; ideological analogies; Georges Bernanos